Paracrine effect of CXCR4‐overexpressing mesenchymal stem cells on ischemic heart injury. (23rd February 2017) - Wu, Shi‐Zheng; Li, Ying‐Lan; Huang, Wei; Cai, Wen‐Feng; Liang, Jialiang; Paul, Christian; Jiang, Lin; Wu, Zhi‐Chao; Xu, Meifeng; Zhu, Ping; Wang, Yigang
Abstract : It has been reported that CXCR4‐overexpressing mesenchymal stem cells (MSC CX4 ) can repair heart tissue post myocardial infarction. This study aims to investigate the MSCCX4‐derived paracrine cardio‐protective signaling in the presence of myocardial infarction. Mesenchymal stem cells (MSCs) were divided into 3 groups: MSC only, MSC CX4, and CXCR4 gene‐specific siRNA‐transduced MSC. Mesenchymal stem cells were exposed to hypoxia, and then MSCs‐conditioned culture medium was incubated with neonatal and adult cardiomyocytes, respectively. Cell proliferation–regulating genes were assessed by real‐time polymerase chain reaction (RT‐PCR). In vitro: The number of cardiomyocytes undergoing DNA synthesis, cytokinesis, and mitosis was increased to a greater extent in MSC CX4 medium‐treated group than control group, while this proproliferative effect was reduced in CXCR4 gene‐specific siRNA‐transduced MSC–treated cells. Accordingly, the maximal enhancement of vascular endothelial growth factor, cyclin 2, and transforming growth factor‐β2 was observed in hypoxia‐exposed MSC CX4 . In vivo: MSCs were labeled with enhanced green fluorescent protein (EGFP) and engrafted into injured myocardium in rats. The number of EGFP and CD31 positive cells in the MSC CX4 group was significantly increased than other 2 groups, associated with the reduced left ventricular (LV) fibrosis, the increased LV free wall thickness, the enhanced angiogenesis, and the improved contractile function. CXCR4 overexpression can mobilize MSCs into ischemic area, whereby these cells can promoted angiogenesis and alleviate LV remodeling via paracrine signaling mechanism.